DETERMINAN PRODUKSI TEMBAKAU PADA LAHAN TEGAL DAN LAHAN GUNUNG DALAM PRESPEKTIF EKONOMI ISLAM (Studi Kasus Di Kecamatan Batumarmar Kabupaten Pamekasan) - Nurul Hidayat; Hertin Khalifatun Nisa Arifah; Kusnul Ciptanila Yuni K; Athi’ Hidayati (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the determinants of tobacco production on upland and mountain lands in the perspective of Islamic economics in Batumarmar District, Pamekasan Regency. In the partial tegal tobacco production regression model, the variable number of seeds has a significant effect on tobacco production. While the variables of land area, amount of fertilizers, pesticides, and labor do not have a significant effect on tobacco production. Then, the results of research on the regression model of tobacco production in mountain areas show that partially the variables of land area, number of seeds, and labor have a significant effect on tobacco production. While the variable amount of fertilizers and pesticides has no significant effect on tobacco production. However, when viewed simultaneously the variables of land area, number of seeds, amount of fertilizers, pesticides, and labor have a significant effect on tobacco production both on upland and mountain lands. Production in the perspective of Islamic economics is producing goods and services that are lawful, do not destroy nature, improve spiritual, mental and physical qualities in a fair way.